(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra one of the eight branches of Ayurveda, focuses on the study and management of poisons and toxic substances. Mooshika Visha or Akuvisha is classified as a type of Jangama Visha. Acharya Susruta identifies eighteen distinct types of Mooshika. The adishtana of Mooshika Visha is considered to be Sukra. The Visha Vaidya Jyotsnika is a renowed Malayalam text that focuses on Visha Chikitsa and offers valuable insights into various formulations and clinical practices. Pathasirishadi Kwatham is a preparation explained in Visha Vaidya Jyotsnika under Mooshika Visha chikithsa adyaya and is indicated in Mooshika damsha. This yoga contains 9 ingredients Patha, Shirisha, Sarpagandha, Vacha, Haridra, Kushta, Mustha, Nagara, Madhuka. This article explores the components, method of preparation, pharmacological properties and evaluates the therapeutic efficacy of the formulation in managing rat poison related diseases like leptospirosis.